BUDIDAYA TANAMAN MELATI DI WILAYAH PESISIRDENGANBAHAN ORGANIK: SARANA PEMBELAJARANEKOLOGI - Handriatni, Ari (Jurnal Cakrawala Pendidikan, 2016)
Many fertile land areas in Indonesia are used for office buildings and new residential areas. Therefore, agricultural .land areas decrease. The agricultural productivity increment through extensive land use should be directed to marginal land such as beaches. Beaches will be suitable for jasmine cultivation with organic fertilizer treatment. This action can also serve as an ecological practice. Academic society, including students, and people in general can do it·together in beaches